A retrospective analysis of the epidemiology and control measures of contagious bovine pleuropneumonia in the northern communal areas of Namibia from 2001 to 2013 - Crafford, Jan Ernst (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.